2015
DOI: 10.1002/cplu.201500386
|View full text |Cite
|
Sign up to set email alerts
|

Study of Multiporphyrin Compounds as Colorimetric Sitting‐Atop Metal Complexes: Synthesis and Photophysical Studies

Abstract: Scheme1.Synthesis of the meso-[4-(pentafluorophenyloxy)phenyl]porphyrins 4-6.Scheme2.Synthesis of diporphyrin 7 and hexaporphyrin 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
2
0
1
Order By: Relevance
“…We have shown that 5-(4-hydroxyphenyl)-10,15,20-triphenylporphyrin ( 1 ) reacts as a nucleophile with hexafluorobenzene or pentafluorophenyl groups to give multiporphyrin derivatives under very mild conditions [67]. As indicated above, porphyrin 2 reacts with nucleophiles to yield nucleophilic aromatic substitution products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that 5-(4-hydroxyphenyl)-10,15,20-triphenylporphyrin ( 1 ) reacts as a nucleophile with hexafluorobenzene or pentafluorophenyl groups to give multiporphyrin derivatives under very mild conditions [67]. As indicated above, porphyrin 2 reacts with nucleophiles to yield nucleophilic aromatic substitution products.…”
Section: Resultsmentioning
confidence: 99%
“…The para -fluorine atoms are selectively substituted by the nucleophile and mono- to tetra-substituted porphyrin derivatives may be obtained. We have reported the synthesis of multiporphyrin compounds via nucleophilic aromatic substitution of fluorine atoms in porphyrin 2 [20] or hexafluorobenzene [67,68]. Using a similar approach, herein we present a simple procedure for the preparation of diporphyrins and pentaporphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, as porfirinas podem ser combinadas com recetores que respondam seletiva e reversivelmente à presença de estímulos externos, e permitam uma fácil e estável incorporação dos compostos em materiais para deteção em fase líquida ou gasosa [8]. As porfirinas têm sido usadas principalmente na deteção de analitos, como iões de metal [9,10], pH do meio [11], aniões [12], oxigénio [13], amoníaco e aminas [14,15], explosivos [16] e outros. Por exemplo, o conjugado porfirina-terpiridina (Figura 3), obtido a partir de 5,10,15,20-tetrafenilporfirina (TPP) e a unidade recetora terpiridina, revelou ser pouco fluorescente quando excitado a 417 nm.…”
Section: Sensores óTicos Baseados Em Porfirinasunclassified